Accelerating Global Deletion of the Abnormal Toxicity Test for vaccines and biologicals. Planning common next steps. A workshop Report. (July 2022) - Viviani, Laura; Reid, Kirsty; Gastineau, Thierry; Milne, Catherine; Smith, Dean; Levis, Robin; Lei, Dianliang; van Ooij, Mark; Gilbert, Philippe Alexandre; Vandeputte, Joris; Xie, Jianxun; Madhuri, Leena; et al.
Abstract: This online workshop Accelerating Global Deletion of the Abnormal Toxicity Test for vaccines and biologicals. Planning common next steps was organized on October 14th, 2021, by the Animal Free Safety Assessment Collaboration (AFSA), the Humane Society International (HSI), the European Federation of Pharmaceutical Industries and Associations (EFPIA), in collaboration with the International Alliance of Biological Standardization (IABS). The workshop saw a participation of over a hundred representatives from international organizations, pharmaceutical industries and associations, and regulatory authorities of 28 countries. Participants reported on country- and region-specific regulatory requirements and, where present, on the perspectives on the waiving and elimination of the Abnormal Toxicity Test. With AFSA, HSI, EFPIA and IABS representatives as facilitators, the participants also discussed specific country/global actions to further secure the deletion of ATT from all regulatory requirements worldwide. Highlights: Update of the current status of the deletion of the Abnormal Toxicity Test (ATT). New stakeholders accepting role of change champions to waive/delete ATT, an obsolete safety test. Agreement to keep enlarging the number of involved stakeholders. Agreement on follow up local and international actions and engagement to further promote the deletion of the test.